FREQUENCY AND PATTERN OF CARDIAC AUTONOMIC NEUROPATHY IN PATIENTS WITH TYPE 2 DIABETES MELLITUS (The Research of Medical Science Review, 2025)
Objective: To determine the “frequency and pattern of cardiac autonomic neuropathy in patients with type 2 diabetes mellitus visiting at tertiary care hospital”.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Liaquat University of Medical and Health Sciences, Jamshoro, over a period of six months.Materials and Methods: A total of 100 patients of either gender with type 2 diabetes mellitus for > 2 years having age >18 years were included. Cardiac Autonomic Neuropathy was determined (as resting heart rate is >100 beats/min and/or presence of arrhythmia, was detected clinically by checking pulse and upon ECG showed irregular pulse and absent p-waves) and its pattern were assessed.Results: Total 100 patients were included. The mean age was 44.8 + 9.8 years with mean duration of the T2DM was 8.4 + 5.4 years. Most of the patients were male 35 (35%) and 65 (65%) were female. Cardiac Autonomic Neuropathy was found in 40 (40%) of the Patients with Type-2 Diabetes Mellitus. Regarding the patterns of the CAN, constipation found in 50 (50%), gastroparasis in 44 (44%), hypertension in 40 (40%), diarrhea in 39 (39%) and erectile dysfunction in 12 (12%) patients with T2DM.Conclusion: The study concludes that frequency of cardiac autonomic neuropathy is quite high (40%) in T2DM patients.